Density and specific gravity of Geronggang (Crotoxylum spp) according to different height levels / Roszana Derani - Derani, Roszana (2004)
The study of density and specific gravity was performed on Geronggang wood (crotoxylum spp). Specific gravity was determined using the maximum moisture content method and density is known as plugs per cubic meter. From the samples were analyzed from the different height level- top, middle and DBH (base). The result indicated that the density was highest at base and lowest at the middle level. On the other hand, specific gravity decreased from the base portion until then to the top portion. Thus specific gravity is inversely related to different height levels.